Promoting gender equality in large enterprises in Slovakia: The perspective of human resource professionals and managers - Jurenková, Veronika; Babeľová, Zdenka Gyurák; Vraňaková, Natália; Čambál, Miloš (Edelweiss Applied Science and Technology, 2026)
The article examines how human resources (HR) professionals and managers in large industrial enterprises in Slovakia perceive gender equality, focusing on awareness, perceived fairness, and experiences with obstacles in implementing equality policies. Gender equality is particularly important in large enterprises, as they employ many people, influence their work and personal lives, and serve as role models for other, often dependent, enterprises. Perceptions of gender equality differ across cultures, reflecting societal values, norms, and structures rather than a universal concept. The research is based on a questionnaire survey, and a descriptive approach was chosen to answer the research questions, defining the research framework. The findings show that the majority of HR professionals and managers are familiar with the issue of gender equality and consider it important, but differences in the perception of this issue persist between men and women. Women more often report only partial awareness, experiences of unequal treatment, and limited career opportunities compared to their male colleagues. The research brings both theoretical and practical implications for the field of HR management and diversity management, especially in the promotion of gender equality, policy making, internal communication, and the development of an inclusive organizational culture in large companies.